EKSTRAK DAUN SALAM DALAM MENINGKATKAN EKSPRESI FIBROBLAST GROWTH FACTOR PADA ULKUS TRAUMATIK RONGGA MULUT - Amrina Rosada; Rochman Mujayanto; Adisty Restu Poetri (Faculty of Dentistry, Universitas Islam Sultan Agung, 2020)
Background: Traumatic ulcers are lesions of the oral mucosa caused by mechanical, chemical, and temperature trauma. Traumatic ulcer treatment aims to reduce inflammation, accelerate the healing process, and reduce pain. Bay leaf has anti-inflammatory pharmacological activities. This study aims to determine the effect of bay leaf extract on the expression of fibroblast growth factor in traumatic ulcer oral mucosa in Wistar rats.Method: This is an experimental research with a post-test only control group design, consisting of four groups with 20 sample of male Wistar rats. All animals were injured using a hot burnisher attached to the labial mucosa for 1 second. The gel was applied twice daily until the 3rd and 5th day after the ulcer has formed. Rat mucosal tissues were analyzed by immunohistochemical staining for FGF expressions. Statistical analysis using SPSS Mann-Whitney test.Result: The results showed the mean of cells expressing FGF in the bay gel extract group on the 3rd and 5th days were 8.4 ± 0.8, and 13.6 ± 0.5. Mann Whitney test results showed P<0.05 there is a significant differential expression of FGF traumatic ulcer oral mucosa of experimental animals on days 3 and 5 compared control group.Conclusion: Bay leaf extract increased FGF expression on days 3 and 5